Green Leverage: How CO2 Emissions Shape Capital Structures in EU Corporations - Dsouza, Suzan; Krishnamoorthy, K.; Franklin, M.; Habibniya, Houshang (International Journal of Energy Economics and Policy, 2025)
This paper examines the interaction between firm leverage and carbon emissions in the European Union, with an emphasis on how corporate environmental performance affects the capital structure of firms. Based on an unbalanced panel of 4,183 firm-year observations from 819 EU listed firms for the period 2010-2024, we use dynamic panel estimation methods (System-GMM) to examine the impact of CO2-equivalent emissions on leverage. The analysis is conditioned on firm-specific financial attributes, profitability, size of firm, tangibility, liquidity, capitalization, and governance factors, including board gender diversity and board size. The empirical findings show a statistically significant negative correlation between firm leverage and carbon emissions, implying that firms with high emissions have the propensity to decrease their debt dependence. This correlation is particularly notable in the case of larger firms, as they are more exposed to regulatory treatment and reputational threats. Financial attributes like increased profitability and equity capitalization also go with lower leverage, while tangibility and liquidity enhance debt capacity. Robustness tests validate consistency of results across firm size groups. The research concludes that carbon emissions are becoming an important determinant of financial decision making, sustaining the importance of environmental performance integration into risk measurement and credit allocation models. These results have important policy implications, calling for more robust carbon disclosure requirements and extending sustainable finance mechanisms. Companies are stimulated to adapt their capital structure for climate goals to promote long-term financial resilience and regulatory compliance in an ESG-sensitive market regime.